Odpowiedzi

Najlepsza Odpowiedź!
2010-02-14T09:49:44+01:00
-3x+5(2x-7)-6(-5x+6)= -3x +10x -35+30x-36 = 37x -71
37* (-1) - 71 = -37-71 - -108

dla x = (-1)

b) 5(a-2b)+4(3a+6b)+12= 5a-10b+12a+24b+12 = 17a + 14b+12
17* 2 + 14* (-5) +12 = 34 - 70 +12 = -24

dla a = 2 i b= (-5)
1 5 1
2010-02-14T09:56:21+01:00
A) -3x+5(2x-7)-6(-5x+6)=-3x+10x-35+30x-36=37x-71
dla x=-1
37*(-1)-71=-37-71=-108

b) 5(a-2b)+4(3a+6b)+12=5a-10b+12a+24b+12=17a+14b+12
dla a = 2 i b= (-5)
17*2+14*(-5)+12=34-70+12=-36+12=-24
2010-02-14T09:56:47+01:00
A) -3x+5(2x-7)-6(-5x+6)
-3x+10x-35+30x-36
37x-71
37*(-1)-71
-37-71=-108

b) 5(a-2b)+4(3a+6b)+12
5a-10b+12a+24b+12
17a+14b+12
17*2+14*(-5)+12
34-70+12
46-70=-24